Ações preventivas e modelos de risco para incêndios florestais fundamentados no conhecimento socioambiental sobre o tema - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The thesis aims to support the choice and definition of preventive measures against vegetation fires, having as prerogative the effects of human activities as the main cause of such events. The present study was developed at the Kalunga Historical and Cultural Heritage Site, which aggregates various aspects of the national context of areas that suffer the effects of fires, adding to the cultural, economic, historical, ecological and social importance of the region. By approaching the theme from the perspective of the anthropic role in fire occurrences, we seek to understand how changes in land use, regional development, social knowledge, cultural habits, assimilation of inherent risks, notions of combat and prevention techniques, cultural and historical formation, access to information and public policies are related to events in the region. Such knowledge can assist decision makers in establishing effective measures to fight unauthorized fires. We established steps for the work that followed the sequence of knowing how the socio-environmental aspects influenced the population's assimilation of vegetation fires, under the legal perspective of land use and culture in the region. Subsequently, we use this information to build a risk model. At this stage, we use, in addition to the previously collected socio-environmental data, land use information and data from technical expertise performed in hot spots registered for the Kalunga Historic Site and Cultural Heritage between 2015 and 2018 to test the effects of human influence on risk of hot spots. We also evaluated how the local actors assimilate the forest fires theme and which aspects define the formation of concepts. In another moment, we simulated a risk model, based on a hypothetical scenario initiated in an area of high risk potential, as previously established, analyzing which resources would be reached and which actions would be best implemented to avoid further damage.
Keywords: Fogo; Desastres ambientais; Prevenção de incêndios florestais; Controle e prevenção de incêndios florestais; Incêndios florestais; Kalunga; Forest fire fighting; Burned; Environmental disasters; Forest fires; Forest fires - Prevention and control; CIENCIAS BIOLOGICAS; OUTROS